2012
DOI: 10.1159/000337749
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Psychotic Symptoms in the General Population: Correlates in an Iranian Urban Area

Abstract: Background: Psychosis exists in the community as a continuum of severity. Here, we examine the correlates of self-reported psychotic symptoms in an urban catchment area of Iran. Sampling and Methods: Two thousand one hundred and fifty-eight participants (age 18–65 years) residing in southern Tehran (the capital city of Iran) were interviewed using the psychoticism and paranoia dimensions of the Symptom Checklist-90-Revised (SCL-90-R) to assess the severity of psychotic symptoms. Other dimensions of the SCL-90-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 85 publications
2
12
0
1
Order By: Relevance
“…Much of the discussion on the public health burden of psychotic disorders is limited to schizophrenia and other psychotic conditions that meet the criteria for distinct DSM diagnoses. The findings from this study and other studies on the health and social consequences of the psychosis spectrum 59,32,33 suggest that psychotic experiences, which are more prevalent than specific psychotic disorders, are also associated with adverse social and health consequences. The link between psychosis, on the one hand, and social well-being and physical health, on the other hand, might be more widespread than suggested by prior research limited to psychotic disorders.…”
Section: Discussionsupporting
confidence: 56%
“…Much of the discussion on the public health burden of psychotic disorders is limited to schizophrenia and other psychotic conditions that meet the criteria for distinct DSM diagnoses. The findings from this study and other studies on the health and social consequences of the psychosis spectrum 59,32,33 suggest that psychotic experiences, which are more prevalent than specific psychotic disorders, are also associated with adverse social and health consequences. The link between psychosis, on the one hand, and social well-being and physical health, on the other hand, might be more widespread than suggested by prior research limited to psychotic disorders.…”
Section: Discussionsupporting
confidence: 56%
“…Sample sizes ranged from N = 11 (Bell & Freeman, 2014) to N = 8576 (Bebbington et al 2013), with the median sample size of n = 90. Except for the population samples in two studies (Sharifi et al 2012; Bebbington et al 2013), all samples were initially self-selected. In two studies, researchers conducted the selection of participants for a second experiment based on participants’ initial paranoia scores (Freeman et al 2005 c ; Green et al 2011) to ensure a range of paranoia scores across the sample.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it seems likely that patients might have difficulties with responding to self-report questionnaires assessing such symptoms. Future research should explore in greater depth the reliability of self-reported psychotic symptoms; although some studies have provided preliminary evidence of reliability and validity [ 28 ]. Future research should also explore the relationship between poor insight and psychotic symptoms in OCD.…”
Section: Discussionmentioning
confidence: 99%
“…Its factor structure and generalizability has been debated [ 27 ], and it has been suggested that the SCL-90-R is a measure of negative affect rather than nine different symptom clusters. Nevertheless, a study has shown that the two subscales psychoticism and paranoid ideation can discriminate patients with psychotic disorder or psychotic symptoms from patients with non-psychotic disorder or psychosis in remission [ 28 ]. Furthermore, these subscales, and new subscales consisting of questions from both subscales, have been utilized as measures of both subclinical psychotic and schizotypal symptoms in several studies [ 15 , 29 34 ].…”
Section: Methodsmentioning
confidence: 99%